Study of Interactions Between Individual Phenolics of Aronia with Barley Beta-Glucan - Lidija Jakobek; Petra Matić; Jozo Ištuk; Andrew R. Barron (Polish Journal of Food and Nutrition Sciences)
Beneficial effects of aronia phenolics are determined by their interactions with dietary fibers, such as beta-glucan. The aim of this research was to study interactions between aronia phenolics and beta-glucan by investigating the adsorption process. Phenolic compounds were extracted from aronia, analyzed using high-performance liquid chromatography, and adsorbed onto beta-glucan at pH 1.5. The adsorption data were modeled by using Langmuir, Dubinin-Radushkevich, and Hill isotherms with a novel non-linear regression developed especially for adsorption isotherms. Aronia phenolics adsorbed onto beta-glucan in amounts 31-250 mg/g (individual anthocyanins), 44-123 mg/g (individual flavonols), and 51 mg/g (neochlorogenic acid). The correlation between adsorption capacities and phenolic content was high (r 2 =0.94), which suggested that the adsorption might be concentration dependent. Modeling with a novel non-linear regression allowed more precise determination of adsorption isotherm parameters. Furthermore, there was a correlation between maximum adsorption capacities predicted by models and measured adsorption capacities (r 2 0.76, 0.81, and 0.34 for Langmuir, Dubinin-Radushevich, Hill isotherms, respectively). The suggested bonds involved in interactions are non-covalent bonds (H bonds, Van der Waals forces). Principal component analysis showed that anthocyanins, flavonols, and phenolic acids could differently behave in the adsorption process, which could be due to differences in the chemical structures (ionic nature of anthocyanins, nonionic nature of flavonols and phenolic acids at low pH). In conclusion, aronia phenolics interacted with beta-glucan by adsorbing onto its surface, and the novel modeling developed by our team was helpful in the interpretation of this process. Interactions should be further studied due to their importance for the beneficial effects of aronia.